Living on Digital Flatlands: Assemblies of Computer Vision - Alex Reid (Rhizomes: Cultural Studies in Emerging Knowledge, 2022)
Drawing on radical media archeology and assemblage theory, this article investigates assemblages of computer vision as they construct new spatiotemporal relations and new capacities for seeing and acting.